Natural history of hepatitis B in perinatally infected carriers. Issue 5 (20th August 2004) - Boxall, E H; Sira, J; Standish, R A; Davies, P; Sleight, E; Dhillon, A P; Scheuer, P J; Kelly, D A
Abstract : Objectives: To establish natural seroconversion rates and incidence of hepatic pathology in perinatally infected hepatitis B carriers. Methods: Seventy three perinatally infected hepatitis B carriers identified through maternal screening were evaluated. Fifty three were born to parents from the Indian subcontinent, nine were Oriental, six were Afro-Caribbean, and five were white. Median follow up was 10.24 (range 2.02–20.16) years. Results: Only three of the children followed up had cleared hepatitis B surface antigen during this period, and 30% of the children had seroconverted to anti-HBe. Seroconversions to anti-HBe were observed in Asian (18/50) and white (4/5) children, but not in Oriental or Afro-Caribbean children. More girls (40%) than boys (23%) had seroconverted, but the difference was not significant. All children were asymptomatic with normal physical examination, growth, and development. Almost half (48%) of the hepatitis B e antigen (HBeAg) positive children had normal hepatic transaminases and liver function. Thirty five liver biopsies were performed in children with active virus replication (HBeAg or hepatitis B virus DNA positive) who were being considered for antiviral treatment as part of a clinical trial and were scored using the Ishak method. Two thirds (62%) of the children had mild hepatitis, 60% had mild fibrosis, and 18% had moderate to severe fibrosis. There was a weak correlation between histological evidence of hepatitis and hepatic transaminase activity, implying that biochemical monitoring of hepatic disease activity may be ineffective. Conclusions: These asymptomatic hepatitis B virus carrier children remain infectious in the medium to long term with notable liver pathology. They should receive antiviral treatment to reduce infectivity and to prevent further progression of liver disease. Hepatic transaminases alone are not a reliable marker of liver pathology, and liver histology is essential before consideration for antiviral treatment.